Exploring the factors influencing customer satisfaction of foodpanda elderly people (above 50 years) - Taher, Ruzlan Reshaila (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.